THE STRATEGY TO IMPROVE THE CHARACTER OF MILITARY ACADEMY CADETS THROUGH THE ROLE OF MENTORS IN SHAPING PROFESSIONAL OFFICERS TO SUPPORT THE MAIN DUTIES OF THE INDONESIAN ARMY: STRATEGI PENINGKATAN KARAKTER TARUNA AKMIL MELALUI PERAN PENGASUH DALAM PEMBENTUKAN PERWIRA PROFESIONAL GUNA MENDUKUNG TUGAS POKOK TNI AD - Haris Puji Prasetiawan; Deni Dadang A.R; Sigit Purwanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The development of professional character among cadets at the Military Academy (Akmil) is a key component in producing officers capable of supporting the core duties of the Indonesian Army (TNI AD). This research examines the optimization of the role of mentors in cadet training, particularly regarding discipline, fighting spirit, and professionalism. Akmil plays a vital role in shaping character, resilient mental attitudes, strong leadership, and technical skills aligned with the nation's defense needs. However, the challenges in character development have become increasingly complex, especially in the past three years (2021–2023). Several cases, such as ethical violations by Second Lieutenant Caj (K) GER and Major Inf BF during the G20 Summit in Bali, and the suicide of Second Lieutenant Arh SS, highlight the need to strengthen character-building efforts. Additionally, the influence of technology on Generation Z adds another layer of challenges to the cadet training process. This study aims to understand the role of mentors in enhancing cadets' character with a focus on professionalism and loyalty, as well as identifying challenges encountered in cadet training. The research employs a qualitative approach with in-depth interviews and field observations, involving cadet mentors, fourth-year cadets, third- year female cadets, and Akmil alumni officers. The findings reveal that the role of mentors has yet to be fully optimized in addressing technological challenges and behavioral changes in Generation Z. Persuasive, instructive, and interactive approaches are identified as primary needs in mentoring. Adaptive strategies, improved communication, and the use of digital media are recognized as key solutions. Furthermore, advanced training in developmental psychology and situational leadership is necessary to enhance mentors' competencies. This study is expected to contribute to the development of a more effective mentoring system at Akmil, aimed at producing TNI AD officers with high competence and integrity.